Comparison of In Vivo Tissue Temperature Profile and Lesion Geometry for Radiofrequency Ablation With High Power–Short Duration and Moderate Power–Moderate Duration: Effects of Thermal Latency and Contact Force on Lesion Formation. (July 2021) - Nakagawa, Hiroshi; Ikeda, Atsushi; Sharma, Tushar; Govari, Assaf; Ashton, John; Maffre, Jennifer; Lifshitz, Alexander; Fuimaono, Kristine; Yokoyama, Katsuaki; Wittkampf, Fred H.M.; Jackman, Warren M.
Abstract : Background: With short radiofrequency (RF) applications, tissue temperature continues to rise after RF termination (thermal latency), which may result in lesion growth after RF termination. The purpose was to compare in vivo tissue temperature profile (thermal latency), lesion size, and the incidence of steam pop and thrombus between RF ablation with very high power–very short RF (90 W/4 s), high power–short RF (50 W/10 s), and moderate power–moderate RF (30 W/30 s) in a canine thigh muscle preparation and beating heart. Methods: In the thigh muscle preparation (5 dogs), a 3.5-mm ablation electrode with 66 or 56 small irrigation holes (QDOT-Micro or ThermoCoolSmartTouch-SF, respectively) was held perpendicular or parallel to the muscle at 10 g or 30 g contact force. Total of 120 RFs were delivered at 90 W/4 s (QDOT catheter), 50 W/10 s, or 30 W/30 s (SF catheter). Electrode temperature, electrode-tissue interface temperature, and tissue temperatures at 3- and 7-mm depths were measured. In 6 closed-chest dogs, total of 72 RFs were delivered in the ventricle at 90 W/4 s, 50 W/10 s, or 30 W/30 s. Results: In the thigh muscle preparation, tissue temperatures and lesion size (depth, diameter, and volume) were the lowest/smallest for RFs at 90 W/4 s, followed by 50 W/10 s, and the greatest for 30 W/30 s. Thermal latency (Δtemperature and duration) was the greatest for RFs at 90 W/4 s, followed by 50 W/10 s, and the smallest for 30 W/30 s ( P <0.01). Effective tissue heating (area under the curve ≥50 °C at 3-mm depth) was observed after RF termination in 88.0±7.6% with 90 W/4 s, 57.7±14.6% with 50 W/10 s, and only 31.9±8.5% with 30 W/30 s ( P <0.01). In beating hearts, lesion size was also the smallest with 90 W/4 s and the greatest with 30 W/30 s RFs. Increasing contact force significantly increased lesion depth in all 3 groups. There was no significant difference in the incidence of steam pop or thrombus between 3 groups. Conclusions: Tissue temperatures and lesion size (depth, diameter, and volume) were the lowest/smallest for RF applications at 90 W/4 s, followed by 50 W/10 s, and the greatest for 30 W/30 s. The greater thermal latency for 90 W/4 s RF applications suggests that a significant portion of lesion is created after RF termination due to conductive tissue heating. Abstract : Supplemental Digital Content is available in the text.